Synthesis and Antidiabetic Evaluation of 5-(2-Methoxy-6-pentadecylbenzylidene)-3-alkyl/aryl substituted thiazolidine-2,4-dione Derivatives - Reddy, M. Upendar; Reddy, M.C. Somasekhara (Asian Journal of Chemistry, 2018)
Compounds containing the thiazolidinedione moiety have been found to exhibit various pharmacological and biological activities viz., COX-2 inhibitor, antihyperglycemic, anti-inflammatory, antioxidant, cytotoxic, antimicrobial etc. The present paper describes the synthesis of 5-(2-methoxy-6-pentadecylbenzylidene)-3-alkyl/aryl-substituted thiazolidine-2,4-dione derivatives (6a-6k) in five synthetic steps utilizing anacardic acid as starting material. The key steps involves (i) methylation of anacardic acid in presence of dimethyl carbonate in sealed tube (ii) methylester reduction in presence of sodium borohydride in refluxing 2-methyl-tetrahydrofuran (iii) oxidation of 1° alcohol in presence of CuBr, 2,2-bipyridine, TEMPO (iv) Condensation reaction of aldehyde with thiazolidinedione followed by alkylation. The newly synthesized 3-substituted N-alkyl/aryl-thiazolidine derivative were evaluated for antidiabetic property (alloxan induced diabetic mice), compounds 6a, 6b, 6c showed significant decrease in fasting blood glucose (FBG) levels (when compared to standard drug with insulin).